2002
DOI: 10.1210/rp.57.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Modulation and Repercussions of Female Reproductive Aging

Abstract: The menopause marks the end of a woman's reproductive life. During the postmenopausal period, plasma estrogen concentrations decrease dramatically and remain low for the rest of her life, unless she chooses to take hormone replacement therapy. During the past 20 years, we have learned that changes in the central nervous system are associated with and may influence the timing of the menopause in women. Recently, it has become clear that estrogens act on more than just the hypothalamus, pituitary, ovary, and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 93 publications
3
75
0
3
Order By: Relevance
“…Young adult Per mutant females show the same oestrous cycle pattern lasting 4-5 days as wild-type females (unpublished data). This regularity in oestrus cyclicity provides a hint for the regularity in the rhythmicity of the luteinizing hormone (LH) surge and ovarian hormones facilitating fertility and embryonal development (Day et al 1989, Diaz et al 2000, Wise et al 2002, Miller et al 2004, Nelson 2005. Contrary to this, adult Clock mutant females reveal prolonged irregular cycles associated with elevated rates of foetal reabsorption and pregnancy failures (Miller et al 2004, Kennaway 2005, Dolatshad et al 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young adult Per mutant females show the same oestrous cycle pattern lasting 4-5 days as wild-type females (unpublished data). This regularity in oestrus cyclicity provides a hint for the regularity in the rhythmicity of the luteinizing hormone (LH) surge and ovarian hormones facilitating fertility and embryonal development (Day et al 1989, Diaz et al 2000, Wise et al 2002, Miller et al 2004, Nelson 2005. Contrary to this, adult Clock mutant females reveal prolonged irregular cycles associated with elevated rates of foetal reabsorption and pregnancy failures (Miller et al 2004, Kennaway 2005, Dolatshad et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…persistent vaginal cornification or leukocytosis, characterise the age-related decline of cyclicity in rats and mice (Nelson et al 1982, Matt et al 1987, Markowska 1999. The initial phases of declining in cyclicity from the 13th month of age onwards are prolonged and irregular cycles and cause a delay in the preovulatory rise of oestradiol (Nelson et al 1981, Wise et al 2002. These prolonged oestrogen secretions in mice and rats have been explained as being a result of incomplete or delayed luteinisation (Nelson et al 1982, Matt et al 1987.…”
Section: Discussionmentioning
confidence: 99%
“…What is more interesting, histamine could induce ovulation in the isolated perfused ovary [39]. In addition, histamine is an important neuro-modulator in the central nervous system which also exerts a role in the regulation of AANM [40]. Some studies focusing on the biological function of histamine at hypothalamus suggested that histamine influenced the secretion of GnRH (gonadotropinreleasing hormone), GTH (gonadotropic hormone), and even estrogen [22,41,42], which are the key molecules for the regulation of female reproduction system.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant information is also currently available about the impact of aging on ovarian steroidogenesis using experimental animal models [203][204][205][206][207][208][209][210][211], to conserve space and given the fact that physiological events connected with the reproductive cyclicity and ovarian sex steroid synthesis in animals, particularly rodents, are significantly different from that of humans, we will restrict our discussion to the aging human ovary only. Also, although aging is known to indirectly influence the ovarian steroid hormone production through modulation of the hypothalamic-pituitaryovarian axis, again, due to space constraints, this aspect of ovarian regulation will not be discussed here, but interested readers may wish to consult several recent excellent reviews that specifically cover this topic [212][213][214][215][216]. Likewise, there are excellent reviews covering the entire spectrum of the pathophysiology of early and late menopause [217][218][219][220][221].…”
Section: Aging and Secretion Of Female Sex-steroidsmentioning
confidence: 99%